Exploring the Impact of Educational Gamification on Students’ Academic Achievement in Learning English at Junior High School - Ismail, Ismail (Maspul Journal of English Studies, 2023)
This research aims to evaluate the impact of implementing gamification in English language teaching on the academic performance of junior high school students, focusing on the context of SMPN 5 Enrekang, Indonesia. The study is based on the understanding that English education plays a crucial role in the development of student's communication skills but faces challenges such as the lack of appeal in conventional teaching methods and the limitations of interactivity in traditional learning. Descriptive analysis results indicate that before the intervention, the average pretest scores of both groups were relatively comparable, demonstrating the equivalence of students' prior knowledge. However, after the intervention, the experimental group showed a significant improvement in post-test scores, while the control group experienced a lower increase. These findings suggest that gamification has a greater positive impact on enhancing the English language proficiency of students compared to traditional teaching methods. This research contributes to the education literature by highlighting the potential of gamification in addressing challenges in English language learning at the junior high school level. The results also provide practical guidance for educators in designing innovative and effective learning strategies to enhance student motivation and academic achievement. Thus, the implementation of gamification is expected to be a step towards improving the holistic and relevant quality of education.